Orientalism and the Figure of the Jew - Librett, Jeffrey S. (Book collections on Project MUSE., 2015)
"This book demonstrates the inextricable entanglement of Orientalism and anti-Judaism in modern German letters. It shows how historicist narratives posit the Orient as fetish in lieu of absent origins, then appropriate this fetish by applying to the East-West relation the Christian supercessionist typology earlier developed to construe the Jewish-Christian relation"--